Pouch volvulus—why adhesions are not always the enemy. (3rd June 2022) - Dionigi, Beatrice; Prien, Christopher; Lavryk, Olga; Lightner, Amy L.; Holubar, Stefan D.; Hull, Tracy
Abstract: Aim: Minimally invasive approaches to proctocolectomy with ileal pouch anal anastomosis have become the standard of care with one benefit being the reduced risk of adhesion‐related complications. However, a lack of pouch adherence to the pelvis can lead to increased mobility as well as volvulization, placing pouch viability at risk. We aimed to describe our institutional experience with pouch volvulus. Methods: Patients who presented with pouch volvulus from 1983 to 2020 were identified through a search of our pelvic pouch registry and enterprise‐wide electronic medical record. Pouch volvulus was defined as a reducible rotation of the J‐pouch on its mesenteric axis with evidence of a properly oriented ileo‐anal anastomosis. Patients with 'twisted pouches' were excluded. Results: In total, 5760 patients underwent ileal pouch anal anastomosis from 1983 to 2020. Six patients (five women) were identified with a diagnosis of 'pouch volvulus' consistent with our definition. The six pouches were constructed utilizing laparoscopic techniques and the mean time from construction to volvulus was 2.36 years. All patients underwent urgent surgery, with a paucity of adhesions noted in five. Reduction and pouch pexy was performed in three and pouch excision in three, with immediate pouch reconstruction in two and end ileostomy creation in one. At a median follow‐up of 9 months, pouch survival was 50%. Conclusions: Pelvic pouches constructed using minimally invasive techniques may be at risk of volvulus due to reduced adhesion development. A high index of suspicion is warranted in pouch patients with obstructive symptomatology. CT imaging may be diagnostic, and prompt surgical intervention may facilitate pouch salvage.